2010
DOI: 10.2105/ajph.2007.130336
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Importance and Feasibility of Including Sexual Orientation in Public Health Surveys: Health Disparities in the Pacific Northwest

Abstract: Important health disparities exist for LGB adults. Sexual orientation can be effectively included as a standard demographic variable in public health surveillance systems to provide data that support planning interventions and progress toward improving LGB health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
276
5
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(301 citation statements)
references
References 18 publications
14
276
5
6
Order By: Relevance
“…Idosos podem se sentir mais inibidos em revelar sua orientação sexual em surveys, o que pode comprometer a confiabilidade desses estudos. 6 A maioria das pesquisas mostra que idosos LGB apresentam pior estado de saúde, quando comparados aos seus pares heterossexuais. Em um estudo populacional que avaliou mais de 1.500 pessoas LGB acima de 50 anos, lés-bicas e bissexuais femininas revelaram maior incapacidade funcional em relação às heterossexuais, pior saúde mental, menos triagens mamográficas, mais obesidade, prevalência de tabagismo, consumo de álcool em excesso e, mesmo após correção de critérios demográficos, mais doenças cardiovasculares.…”
Section: Estudos Com a População Idosaunclassified
See 3 more Smart Citations
“…Idosos podem se sentir mais inibidos em revelar sua orientação sexual em surveys, o que pode comprometer a confiabilidade desses estudos. 6 A maioria das pesquisas mostra que idosos LGB apresentam pior estado de saúde, quando comparados aos seus pares heterossexuais. Em um estudo populacional que avaliou mais de 1.500 pessoas LGB acima de 50 anos, lés-bicas e bissexuais femininas revelaram maior incapacidade funcional em relação às heterossexuais, pior saúde mental, menos triagens mamográficas, mais obesidade, prevalência de tabagismo, consumo de álcool em excesso e, mesmo após correção de critérios demográficos, mais doenças cardiovasculares.…”
Section: Estudos Com a População Idosaunclassified
“…3 Apesar desse crescimento acelerado, existem poucos estudos que avaliam as condições de saúde e as especificidades do envelhecimento da população de idosos LGB. 4 Em relação a adolescentes e adultos, há inúmeros estudos na atualidade que têm evidenciado diferenças em morbidades e fatores de risco para diversas doenças na população LGB, quando comparada a pessoas heterossexuais, tais como: maior taxa de tabagismo, [5][6][7] uso excessivo de álcool e maior tendência à obesidade, 5,6,8 maior frequência de uso de drogas, 7 maior prevalência de doenças cardiovasculares 5 e maior chance de desenvolver câncer de mama. 8,9 No entanto, a maioria desses estudos foi realizada com indivíduos de 18 a 50 anos.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Some of this research has reported that when compared with heterosexual men, gay men have a higher incidence of eating disorders (Russell & Keel, 2002); suicide and suicide attempts (Skegg, Nada-Raja, Dickson, Paul, & Williams, 2003); depression, panic attacks, and psychological distress (Cochran, Sullivan, & Mays, 2003); and have an elevated risk for anxiety, mood, and substance use disorders (Bostwick, Boyd, Hughes, & McCabe, 2009). Gay men, especially those attached to gay communities, are also reported to be more likely to use nonprescription drugs, including alcohol, at higher levels ( Van de Ven, Rawstorne, & Treloar, 2002) and more likely to smoke tobacco than heterosexual men (Dilley, Simmons, Boysun, Pizacani, & Stark, 2010).…”
Section: Introductionmentioning
confidence: 99%